AB1528-HPR FULL BODY HAPTIC BODYSUIT - AN INSTRUMENT TO MEASURE THE RANGE AND SPEED OF MOTION IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS (axSpA) - PRELIMINARY RESULTS - Weber, N.; Lennartz, Rebecca; Knitza, Johannes; Bayat, Sara; Sadeghi, Misha; Ibrahim, Alzhraa; Karatastan, C.; Sudhakar, A.; Ramzezanzadegan, N.; Kahali, S.; Mirzayev, A.; Schuster, Louis; et al. (Annals of the Rheumatic Diseases, 2022)
Movement of the spine is restricted in axial spondyloarthritis (axSpA) [1]. Spine function is usually assessed by the Bath Ankylosing Spondylitis Metrology Index (BASMI), which is based on a limited set of defined motions that are measured semiquantitatively in the spatial dimension but not in the temporal dimension. Sensor-based measurement of spine function in axSpA patients is in its infancy but may provide a deeper and more detailed understanding of the impact of axSpA on the impairment of spine function [2,3]. In theory, unbiased full body assessment of spine motion may open a new dimension in function analysis in axSpA.<br

ACCURACY AND PERFORMANCE OF A HANDHELD ULTRASOUND DEVICE TO ASSESS ARTICULAR AND PERIARTICULAR PATHOLOGIES IN PATIENTS WITH INFLAMMATORY ARTHRITIS - Corte, G.; Bayat, Sara; Tascilar, Koray; Valor, L.; Schuster, Louis; Knitza, Johannes; Schett, Georg; Kleyer, Arnd; Simon, David (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Accuracy and tolerability of self-sampling of capillary blood for analysis of inflammation and autoantibodies in rheumatoid arthritis patients-results from a randomized controlled trial - Knitza, Johannes; Tascilar, Koray; Vuillerme, Nicolas; Eimer, Ekaterina; Matusewicz, Paul; Corte, Giulia; Schuster, Louis; Aubourg, Timothee; Bendzuck, Gerlinde; Korinth, Marianne; Elling-Audersch, Corinna; Kleyer, Arnd; et al. (Arthritis Research & Therapy, 2022)
Background: Rheumatoid arthritis (RA) requires early diagnosis and tight surveillance of disease activity. Remote self-collection of blood for the analysis of inflammation markers and autoantibodies could improve the monitoring of RA and facilitate the identification of individuals at-risk for RA.
CRIS-Team WoS Importer:2022-06-10
Keywords: Self-sampling; Capillary blood; Rheumatoid arthritis; Disease activity

Association of Structural Entheseal Lesions With an Increased Risk of Progression From Psoriasis to Psoriatic Arthritis - Simon, David; Tascilar, Koray; Kleyer, Arnd; Bayat, Sara; Kampylafka, Eleni; Sokolova, Maria; Zekovic, Ana; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, Klaus; Sticherling, Michael; et al. (Arthritis and Rheumatology, 2021)
Objective. To test whether the presence of structural entheseal lesions in psoriasis patients influences the risk of progression to psoriatic arthritis (PsA).
CRIS-Team WoS Importer:2022-01-07

A virtual reality based app to educate health care professionals and medical students about inflammatory arthritis: Feasibility study - Klemm, Philipp; Kleyer, Arnd; Tascilar, Koray; Schuster, Louis; Meinderink, Timo; Steiger, Florian; Lange, Uwe; Möller-Ladner, Ulf; Knitza, Johannes; Sewerin, Philipp; Mucke, Johanna; Pfeil, Alexander; et al. (JMIR Serious Games, 2021)
Background: Inflammatory arthritides (IA) such as rheumatoid arthritis or psoriatic arthritis are disorders that can be difficult to comprehend for health professionals and students in terms of the heterogeneity of clinical symptoms and pathologies. New didactic approaches using innovative technologies such as virtual reality (VR) apps could be helpful to demonstrate disease manifestations as well as joint pathologies in a more comprehensive manner. However, the potential of using a VR education concept in IA has not yet been evaluated. Objective: We evaluated the feasibility of a VR app to educate health care professionals and medical students about IA. Methods: We developed a VR app using data from IA patients as well as 2D and 3D-visualized pathological joints from X-ray and computed tomography generated images. This VR app (Rheumality) allows the user to interact with representative arthritic joint and bone pathologies of patients with IA. In a consensus meeting, an online questionnaire was designed to collect basic demographic data (age, sex); profession of the participants; and their feedback on the general impression, knowledge gain, and potential areas of application of the VR app. The VR app was subsequently tested and evaluated by health care professionals (physicians, researchers, and other professionals) and medical students at predefined events (two annual rheumatology conferences and academic teaching seminars at two sites in Germany). To explore associations between categorical variables, the ? 2 or Fisher test was used as appropriate. Two-sided P values =.05 were regarded as significant. Results: A total of 125 individuals participated in this study. Among them, 56% of the participants identified as female, 43% identified as male, and 1% identified as nonbinary; 59% of the participants were 18-30 years of age, 18% were 31-40 years old, 10% were 41-50 years old, 8% were 51-60 years old, and 5% were 61-70 years old. The participants (N=125) rated the VR app as excellent, with a mean rating of 9.0 (SD 1.2) out of 10, and many participants would recommend use of the app, with a mean recommendation score of 3.2 (SD 1.1) out of 4. A large majority (120/125, 96.0%) stated that the presentation of pathological bone formation improves understanding of the disease. We did not find any association between participant characteristics and evaluation of the VR experience or recommendation scores. Conclusions: The data show that IA-Targeting innovative teaching approaches based on VR technology are feasible.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Feasibility; Inflammatory arthritis; Psoriatic arthritis; Rheumatoid arthritis; Virtual reality

Baricitinib Improves Bone Biomechanical Properties in Rheumatoid Arthritis (RA) - Results of a Prospective Interventional Study - Kemenes, Stephan; Hartmann, Fabian; Tascilar, Koray; Simon, David; Bayat, Sara; Krönke, Gerhard; Mendez, Larissa Valor; Schuster, Louis; Liphardt, Anna-Maria; Schett, Georg; Kleyer, Arnd (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

BARICITINIB LEADS TO RAPID AND PERSISTENT RESOLUTION OF SYNOVITIS AS MEASURED BY HAND MRI IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS (RA) FAILING CS/BDMARD THERAPY - Kemenes, S.; Bayat, Sara; Simon, David; Krönke, Gerhard; Bohr, D.; Valor, L.; Hartmann, F.; Schuster, Louis; Tascilar, Koray; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Cinematic Rendering Enables Depiction of Bone Anabolic Effects in Patients Treated with Baricitinib - Bayat, Sara; Simon, David; Schuster, Louis; Schett, Georg; Kleyer, Arnd (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Corrigendum to “Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography” [Ann. Anat. 252 (2024) 152207] (Annals of Anatomy (2024) 252, (S0940960223001620), (10.1016/j.aanat.2023.152207)) - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The authors regret in the article by Singh et al. in volume 252;152207, February 2024, of Annals of Anatomy, the following change should be made in the acknowledgement section: 1. The present work was performed in (partial) fulfillment of the requirements for obtaining the degree of Dr. med (SS).The additional information provided does not influence the conclusions of the study. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-31

Early detection of rheumatoid arthritis through patient empowerment by tailored digital monitoring and education: a feasibility study - Pfeuffer, Nicola; Hartmann, Fabian; Grahammer, Manuel; Simon, David; Schuster, Louis; Kuhn, Sebastian; Krönke, Gerhard; Schett, Georg; Knitza, Johannes; Kleyer, Arnd (Rheumatology International, 2025)
Patients at risk for rheumatoid arthritis (RA) describe fluctuating and nonspecific symptoms, making it difficult to quantify symptom burden and recognize RA progression. This study aimed to assess feasibility and diagnostic value of a multimodal digital self-monitoring program in preclinical RA. This prospective cohort study included individuals at-risk for RA, who first watched self-produced educational videos about (preclinical) RA and joint self-examination techniques and then started the REMOTRA symptom monitoring. Key outcomes measured included patient acceptance (Net Promoter Score: NPS), monitoring program usability (System usability scale: SUS), monitoring adherence, diagnostic accuracy, and reported symptom burden. A total of 43 participants (65.9% female, mean age 50.1 years) were enrolled. The educational and self-examination videos received NPS ratings of 54.4 and 31.6, respectively. The monitoring software received usability scores of 88.1/100 (SD: 5.5) at three months and 85.4/100 (SD: 16.0) at 6 months. 24/41 (58.5%) completed all questionnaires, and the average app usage was 4.8 months (SD: 1.8). None of the patients with a REMOTRA score below 10 developed RA, yielding a negative predictive value and sensitivity of 100%. However, the positive predictive value was 12%, and the specificity was 42.1%. Analgesic and cortisone usage was reported by 58.5% and 29.3% of participants, respectively. The strong patient acceptance, ease of use, and high adherence rates, combined with encouraging diagnostic outcomes, underscore the potential of this personalized digital monitoring and education approach. These findings suggest that further validation through multicenter studies is warranted.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Digital health; Patient education; Remote monitoring; Rheumatoid arthritis

EVALUATION OF A VIRTUAL REALITY-BASED APPLICATION TO EDUCATE HEALTHCARE PROFESSIONALS AND MEDICAL STUDENTS ABOUT INFLAMMATORY ARTHRITIS - Klemm, Philipp; Kleyer, Arnd; Tascilar, Koray; Schuster, Louis; Meinderink, Timo; Steiger, F.; Lange, Uwe; Müller-Ladner, Ulf; Knitza, Johannes; Sewerin, Philipp; Mucke, Johanna; Pfeil, Alexander; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Purpose: To evaluate the feasibility of studying the vascular supply of the orbital and palpebral lobes of the human lacrimal gland using micro-computed tomography (micro-CT) and microscopic dissection. Methods: The lacrimal gland artery of a fresh parasagittalized cadaver head (male, aged 76 years) was infused with a lead oxide-latex mixture near the occipital pole of the gland. The entire lacrimal gland was imaged using micro-CT and 3D cinematic rendering (CR) and then dissected under a surgical microscope. Results: Micro-CT and CR images showed well-demarcated internal vascular branches of the lacrimal artery and their distribution within the orbital and palpebral lobes. The entire course of the artery and its branches could be visualized by CR and microscopic dissection, with the former showing better spatial orientation and finer branching. The main artery runs along the free edge of the aponeurosis of the levator palpebrae superior muscle and lies in the isthmus portion of the gland (between the orbital and palpebral lobes). The branches of the main lacrimal artery include one branch to the orbital adipose tissue just before entering the gland, two branches to the orbital lobe (medial and lateral), and two branches to the palpebral lobe (medial and lateral). The main artery terminates as palpebral and orbital lobe branches in the lateral half of the lacrimal gland. Conclusion: Latex and contrast-enhanced micro-CT is very well suited to visualize the vascular anatomy of the lacrimal artery within the gland. A large number of lacrimal gland examinations using the method presented here are required to demonstrate and understand the variability of the vascular anatomy of the human lacrimal gland.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Anatomy; CT; Dry eye disease; Lacrimal artery; Lacrimal gland

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Messung des krankheitsbezogenen Wissens von Patient*innen mit axialer Spondyloarthritis – Entwicklung und Anwendung des G-ASKQ7-Fragebogens - Schuster, Louis; Henes, Jörg; Diener, Matthias; Mühlensiepen, Felix; Andreica, Ioana; Hueber, Axel; Schett, Georg; Knitza, Johannes (Zeitschrift für Rheumatologie, 2024)
Hintergrund/Ziel: Patientenedukation ist integraler Bestandteil der Behandlung von Patient*innen mit axialer Spondyloarthritis (axSpA). Allerdings sind die verfügbaren validen Messinstrumente zur Erhebung des krankheitsbezogenen Wissens veraltet und im Falle der axSpA nur in englischer Sprache verfügbar. Die Ziele dieser Studie waren daher (1) die Entwicklung eines geeigneten deutschsprachigen Instruments zur Messung krankheitsspezifischen Wissens bei axSpA-Patient*innen und (2) die Pilotierung dieses Instruments. Methoden: Verfügbare Messinstrumente speziell für die axSpA wurden von einem Expertengremium geprüft, und ein Entwurf des aktuellen G‑ASKQ7 wurde abgestimmt. Nach Evaluation der Augenscheinvalidität und entsprechenden Anpassungen wurden erwachsene konsekutive axSpA-Patient*innen der rheumatologischen Hochschulambulanz des Universitätsklinikums Erlangen gebeten, den Fragebogen auszufüllen. Es wurden Korrelationen zwischen dem erreichten Summenscore und weiteren erhobenen Parametern (Alter, Geschlecht und Krankheitsdauer) untersucht. Ergebnisse: Der entwickelte G‑ASKQ7-Fragebogen umfasst 7 Fragen, wurde als leicht verständlich bewertet und innerhalb von durchschnittlich 6,3 ±2,0 min ausgefüllt; 65 axSpA-Patient*innen (36 Frauen; mittleres Alter: 45,3 ± 12,4 Jahre; mittlere Erkrankungsdauer: 8,6 ±7,3 Jahre) beantworteten den finalen Fragebogen. Der G‑AKSQ7-Mittelwert lag bei 17,8/25 und war bei Frauen (19,0/25) signifikant höher als bei Männern (16,3/25) (p = < 0,05). Am häufigsten wurde Frage 7 (79,3 %) mit Hinblick auf das Selbstmanagement der Erkrankung korrekt beantwortet. Frage 4 mit Blick auf die Messung der Krankheitsaktivität wurde am schlechtesten beantwortet (55,8 %). Es konnte keine signifikante Korrelation zwischen der Krankheitsdauer (p = 0,57; r = 0,07; Pearson-Korrelationstest) oder dem Alter (p = 0,67; r = −0,05; Pearson-Korrelationstest) und dem krankheitsbezogenen Wissen festgestellt werden. Diskussion: Der G‑ASKQ7 bietet erstmals ein deutschsprachiges Instrument zur Ermittlung des krankheitsspezifischen Wissens von axSpA-Patient*innen. Durch eine routinemäßige Erhebung mittels G‑ASKQ7 kann der individuelle Wissensbedarf von Patient*innen niedrigschwellig ermittelt werden, und Edukationsinhalte können gezielt auf Patient*innen abgestimmt werden. Eine kontinuierliche Aktualisierung und weitere Evaluationsstudien sind erforderlich.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Axial spondyloarthritis; Health competence; Health services research; Patient education; Self-management

PATIENT SELF-SAMPLING IN RHEUMATOID ARTHRITIS: RESULTS FROM A RANDOMIZED CONTROLLED TRIAL - Knitza, Johannes; Tascilar, Koray; Vuillerme, N.; Vogt, E.; Matusewicz, P.; Corte, Giulia; Schuster, Louis; Aubourg, T.; Bendzuck, G.; Korinth, M.; Elling-Audersch, C.; Kleyer, Arnd; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
Background Rheumatoid arthritis (RA) requires early diagnosis and tight surveillance of disease activity. Patient self-sampling of blood for the analysis of autoantibodies and inflammation markers could facilitate the identification of patients at-risk for RA and improve tight disease monitoring [1]. Objectives A randomized, controlled trial to evaluate the feasibility, acceptability and accuracy of an upper arm self-sampling device (UA) and finger prick-test (FP) to measure capillary blood from RA patients for C-reactive protein (CRP) levels and the presence of IgM rheumatoid factor (RF IgM) and anti-cyclic citrullinated protein antibodies (anti-CCP IgG). Methods 50 RA patients were randomly assigned in a 1:1 ratio to self-collection of capillary blood via UA or FP. Venous blood sampling (VBS) was performed as gold standard in both groups to assess the concordance of CRP levels as well as RF IgM and CCP IgG. General acceptability and pain during sampling were measured and compared between UA, FP and VBS. The number of attempts for successful sampling, requests for assistance, volume and duration of sample collection were also assessed. Results 49/50 (98%) patients were able to successfully collect capillary blood. Overall agreement between capillary and venous analyses for CRP (0.992), CCP IgG (0.984) and RF IgM (0.994) were good. In both groups 4/25 (16%) needed a second attempt and 8/25 (32%) in the UA and 7/25 (28%) in the FP group requested assistance. Mean pain scores for capillary self-sampling (1.7/10 ± 1.1 (UA) and 1.9/10 ± 1.9 (FP)) were lower on a numeric rating scale compared to venous blood collection (UA: 2.8/10 ± 1.7; FP: 2.1 ± 2.0). UA patients were more likely to promote the use of capillary blood sampling (net promoter score: +28% vs. -20% for FP) and were more willing to perform blood collection at home (60%) vs. 32% for FP). Conclusion This study shows that self-sampling is accurate, feasible and well accepted among patients. The implementation could allow tight remote monitoring of disease activity as well as identifying patients at-risk for RA and potentially other rheumatic disease
CRIS-Team WoS Importer:2022-11-04

Performance of a handheld ultrasound device to assess articular and periarticular pathologies in patients with inflammatory arthritis - Corte, Giulia; Bayat, Sara; Tascilar, Koray; Valor-Mendez, Larissa; Schuster, Louis; Knitza, Johannes; Fagni, Filippo; Schett, Georg; Kleyer, Arnd; Simon, David (Diagnostics, 2021)
The purpose of this study was to assess the accuracy and performance of a new handheld ultrasound (HHUS) machine in comparison to a conventional cart-based sonographic machine in patients with inflammatory arthritis (IA). IA patients with at least one tender and swollen joint count were enrolled. US was performed on the clinically affected joints using a cart-based sonographic device (Samsung HS40) and a HHUS device (Butterfly iQ). One blinded reader scored all images for the presence of erosions, bony enlargement, synovial hypertrophy, joint effusion, bursitis, tenosynovitis, and enthesitis. Synovitis was graded (B mode and power Doppler (PD)) by the 4-level EULAR-OMERACT scale. To avoid bias by the blinded reader, we included 67 joints of two healthy volunteers in the evaluation. We calculated the overall concordance and the concordance by type of joint and pathological finding. We also measured the time required for the US examination per joint with both devices. Thirty-two patients (20 with RA, 10 with PsA, and one each with gout and SLE-associated arthritis) were included, and 186 joints were examined. The overall raw concordance in B mode was 97% (κappa 0.90, 95% CI (0.89, 0.94)). In B mode, no significant differences were found in relation to type of joint or pathological finding examined. The PD mode of the HHUS device did not detect any PD signal, whereas the cart-based device detected a PD signal in 61 joints (33%). The portable device did not offer any time savings compared to the cart-based device (47.0 versus 46.3 s). The HHUS device was accurate in the assessment of structural damage and inflammation in patients with IA, but only in the B mode. Significant improvements are still needed for HHUS to reliably demonstrate blood flow detection in PD mode.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Handheld ultrasound device; Inflammatory arthritis; Medical ultrasound; Musculoskeletal ultrasound

„Rheuma (be-)greifen“ – ein multimodales Lehrkonzept zur Verbesserung der rheumatologischen Lehre für Studierende der Humanmedizin - Schuster, Louis; Valor-Mendez, Larissa; Wacker, Jochen; Dannhardt-Thiem, V.; Schmidt, A.; Knitza, Johannes; Simon, David; Manger, Bernhard; Schett, Georg; Kleyer, Arnd (Zeitschrift für Rheumatologie, 2023)
Background: The German Society for Rheumatology, through its campaign Rheuma2025, aims to improve student teaching in order to ensure patient care for rheumatological patients in the future. Objective: To assess whether a combination of traditional and innovative educational methods provide both an improvement in the quality of teaching and an increase in the attractiveness of rheumatology as a discipline. Material and methods: Establishment of the teaching concept “Rheuma (be-)greifen” consisting of five modules on patient history taking with acting patients, musculoskeletal ultrasound, arthrocentesis, 3D printing of pathological joints and virtual reality applications based on real patient cases in the curricular teaching of medical students. Results: The evaluation of the teaching concept with 93 students of medicine showed a consistently high acceptance of all modules, which were rated as very effective or rather effective. Direct patient-related modules, such as history taking with acting patients, musculoskeletal ultrasound and arthrocentesis, received even higher acceptance than the visualization methods utilizing 3D printing and virtual reality. Conclusion: Innovative teaching methods can help to improve the acceptance of teaching in the field of rheumatology, especially when combined with classical teaching contents.
CRIS-Team Scopus Importer:2023-08-11
Keywords: 3D printing; Medical education; Rheumality©; Rheumatology; Virtual reality

STRUCTURAL ENTHESEAL LESIONS IN PSORIASIS PATIENTS ARE ASSOCIATED WITH AN INCREASED RISK OF PROGRESSION TO PSORIATIC ARTHRITIS - A PROSPECTIVE COHORT STUDY - Simon, David; Tascilar, K.; Kleyer, Arnd; Bayat, Sara; Kampylafka, E.; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, K.; Sticherling, Michael; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Understanding Ankylosing Spondylitis - - Kleyer, Arnd; Pachowsky, Milena; Schuster, Louis; Valor-Mendez, Larissa; Schett, Georg; Hueber, Axel; Simon, David (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

"Virtual Rheumatology" A new Teaching Concept for the Rheumatology of Future? - Kleyer, Arnd; Simon, David; Hartmann, F.; Schuster, Louis; Hueber, Axel (Zeitschrift für Rheumatologie, 2019)
CRIS-Team WoS Importer:2019-03-26